2005
DOI: 10.1016/j.jastp.2005.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of infra-red radiation by atmospheric molecular cluster-ions

Abstract: Results from previous laboratory experiments indicate that both the protonated water dimer H 3 O + (H 2 O), and molecular cluster-ions, X + (H 2 O) n absorb infra-red (IR) radiation in the water vapour continuum region between 4-14µm (2500-714cm -1 ).Protonated water clusters are a common species of atmospheric molecular cluster-ion, produced by cosmic rays throughout the troposphere and stratosphere. Under clearsky conditions or periods of increased atmospheric ionisation, such as solar proton events, the IR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 29 publications
(39 reference statements)
1
52
0
Order By: Relevance
“…Ambient water vapour containing 10 17 [18]. This greatly enhances the possible contribution of water clusters to radiation absorption and emission and has been argued to explain the strong far-infrared and submillimeter absorption of radiation in Earth's atmosphere [3,4].…”
Section: Electrical Dipole Moments Of Water Nanoclustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambient water vapour containing 10 17 [18]. This greatly enhances the possible contribution of water clusters to radiation absorption and emission and has been argued to explain the strong far-infrared and submillimeter absorption of radiation in Earth's atmosphere [3,4].…”
Section: Electrical Dipole Moments Of Water Nanoclustersmentioning
confidence: 99%
“…Scientific interest in water nanoclusters has been motivated by their possible roles in biology [1,2], atmospheric science [3,4], and astrophysics [5], as well as by their relevance to the structure and properties of liquid water [6]. In a recent letter by this author and collaborators [7], it has been suggested that because of their large electric dipole moments, protonated water clusters such as (H 2 O) 21 H + shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…5-7, 10, 22, 43, 44 Water complexes can be diffuse absorbers of solar radiation, contributing to atmospheric heating, an effect resulting from changes occurring upon complex formation in the IR and near IR spectra of constituent monomers. 7,8,[10][11][12]45 Intermolecular interactions responsible for complex formation cause shifts and increased linewidth in ro-vibrational spectra of water complexes compared with the constituent monomers, thereby enhancing their "greenhouse" gas potential. 8,11 Only water complexes with abundant atmospheric gases have atmospheric concentrations large enough to affect radiative transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments showed that atmospheric cluster-ions can absorb radiation in the 9-12 µm range of the infra-red (IR) spectrum [10]. However, it has not been possible to detect any relationship between atmospheric ionisation and the downwelling broadband IR radiation in clear sky at the Snowdon Summit site, due to atmospheric temperature effects modulating both the muon data and downwelling IR.…”
Section: Atmospheric Ionisation and Downwelling Longwave Radiationmentioning
confidence: 99%